2022
DOI: 10.1371/journal.pone.0272703
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics of peripheral immune cells of Myalgic encephalomyelitis/chronic fatigue syndrome via transmission electron microscopy: A pilot study

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex chronic multi-systemic disease characterized by extreme fatigue that is not improved by rest, and worsens after exertion, whether physical or mental. Previous studies have shown ME/CFS-associated alterations in the immune system and mitochondria. We used transmission electron microscopy (TEM) to investigate the morphology and ultrastructure of unstimulated and stimulated ME/CFS immune cells and their intracellular organelles, including mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 195 publications
1
13
0
Order By: Relevance
“…Moreover, both IL22 and IL10 protect gut mucosal immunity and act on the same receptors, loss of these cytokines may trigger the pathogenesis of long COVID and ME/CFS [301,302]. These findings are in line not only with our earlier hypothesis but also with the results novel studies that have connected dysfunctional efferocytosis with fatiguing illnesses, including FM, ME/CFS, and GWIs [303][304][305].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, both IL22 and IL10 protect gut mucosal immunity and act on the same receptors, loss of these cytokines may trigger the pathogenesis of long COVID and ME/CFS [301,302]. These findings are in line not only with our earlier hypothesis but also with the results novel studies that have connected dysfunctional efferocytosis with fatiguing illnesses, including FM, ME/CFS, and GWIs [303][304][305].…”
Section: Discussionsupporting
confidence: 89%
“…CD41a is a component of GPIIb/IIIa complex – the platelet receptor that binds fibrinogen and von Willebrand factor, and mediates platelet adhesion and aggregation, and clotting. Further indications of platelet hyperactivity come from a recent study using transmission electron microscopy, where significant platelet spreading and aggregation was documented in ME/CFS samples [ 172 ]. In contrast, a study from 2006 found neither platelet hyperactivation nor hypercoagulation in their ME/CFS cohort [ 173 ].…”
Section: Haematological Findingsmentioning
confidence: 99%
“…It is plausible to hypothesize that viruses (and potentially other microbes) are contributing to the clotting pathology observed in ME/CFS individuals [ 42 , 43 , [170] , [171] , [172] ]. Herpes viruses, the virus types most implicated in ME/CFS, are known to influence coagulation in a prothrombotic manner [ [308] , [309] , [310] ].…”
Section: Viruses: How Are They Involved and Where Are They Hiding?mentioning
confidence: 99%
“…In addition to its central role in generating over 95% of a cell's energy through ATP, changes in mitochondrial morphology and function accompany lymphocyte differentiation and activation 21 , with mitochondria driving cytokine production 22 , thereby linking energy metabolic deficits in immune cells with chronic inflammation. Along these lines, studies have hypothesized and identified signatures of mitochondrial dysfunction among CFS and LC patients, including down-regulation of host mitochondrial genes even after COVID-19 recovery 23 , altered mitochondrial morphology 24 in ME/CFS donor T cells, decreases in mitochondrial membrane potential 25 among recovered COVID-19 subjects' lymphocytes, and redox dysregulation in both ME/CFS and COVID-19 26 .…”
Section: Introductionmentioning
confidence: 99%